2013
DOI: 10.1021/jz402512g
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Coherence through Variation of Intermolecular Distances in a Series of Molecular Dimers

Abstract: Quantum coherences between electronically excited molecules are a signature of entanglement and play an important role for energy transport in molecular assemblies. Here we monitor and analyze for a homologous series of molecular dimers embedded in a solid host the emergence of coherence with decreasing intermolecular distance by single-molecule spectroscopy and quantum chemistry. Coherent signatures appear as an enhancement of the purely electronic transitions in the dimers which is reflected by changes of fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
53
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 47 publications
2
53
0
Order By: Relevance
“…Very recently, this series of PBI dimers has also been investigated by single-molecule spectroscopy in condensed state on thin films by Baschéand co-workers. 144 These authors have shown that the electronic coupling and static disorder control the quantum-mechanical coherence between the electronically excited PBI units in these dimers. These coherences were clearly found to influence fluorescence lifetimes as well as the emission spectra.…”
Section: Rigid Pbi Dimersmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, this series of PBI dimers has also been investigated by single-molecule spectroscopy in condensed state on thin films by Baschéand co-workers. 144 These authors have shown that the electronic coupling and static disorder control the quantum-mechanical coherence between the electronically excited PBI units in these dimers. These coherences were clearly found to influence fluorescence lifetimes as well as the emission spectra.…”
Section: Rigid Pbi Dimersmentioning
confidence: 99%
“…These coherences were clearly found to influence fluorescence lifetimes as well as the emission spectra. 144 Further interesting photophysical studies of in-line arranged PBI ensembles, in particular with trimer analogues similar to 2-1a, were performed by Matile, 145 Hulst, Hoogenboom, and Garcia-Parajo, 146−149 Mullen, De Schryver, and Hofkens, 150 Debije and Schenning,151,152 Herz, 153 and their co-workers. It has been convincingly shown that the degree of PBI dye alignment in a nematic liquid-crystalline host could be appreciably improved by attaching PBI units through rigid N−N linkage as in PBI dimer 2-1a and its trimer analogue.…”
Section: Rigid Pbi Dimersmentioning
confidence: 99%
“…We would be satisfied and delighted if the structure and organization of this composition could potentially guide readers to choose the appropriate donor molecules on the basis of the corresponding structure of their own acceptors as well as consequently obtain a much higher device performance with further optimization. transport ability, common small molecules such as perylene diimides (PDI), [112,[116][117][118][119][120][121][122][123][124][125] naphthalene diimides (NDI), [126][127][128][129] phthalimide (PhI), [130][131][132][133][134] diketopyrrolopyrrole (DPP), [135][136][137][138][139][140][141][142][143] and so on, [144][145][146][147][148] are widely employed as the electron deficient materials. The strong electron-withdrawing property of imides also makes them excellent candidates for functionalizing aromatic rings to create building blocks for electron-deficient photoactive materials.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, large multichromophoric systems with great potential for applications appear very heterogeneous. Therefore many research activities have been focussed on small model systems with linear, [18][19][20] cofacial, 21 zigzag, [22][23][24][25] cyclic, 26 or square geometries 27 as well as dendrimers consisting of 2 or more subunits. 28,29 Recently, we have studied dyads consisting of PBI antenna molecules that were covalently linked to a fullerene by a flexible hexyl spacer and found an efficient energy transfer from the antennae to the fullerene, while charge-transfer processes play only a minor role.…”
Section: Introductionmentioning
confidence: 99%